Mendelssohns Sololieder: Eine Standortbestimmung - Gesse-Harm, Sonja (Die Musikforschung, 2022)
Although the catalogue of the works of Felix Mendelssohn Bartholdy lists 129 solo songs, musicological interest in this sizeable oeuvre is very limited. In general, these compositions are criticized as sentimental art of the bourgeoisie and are not considered as equal to the innovative and important achievements of Franz Schubert or Robert Schumann. Nevertheless, Mendelssohn’s interest in the close connection of music and poetry is striking, and across his compositional output – including compositions with orchestra – the structural imprint of the Lied can be found. This paper first charts the low interest in this part of Mendelssohn’s oeuvre. In a second step it seeks to describe the characteristics of Mendelssohnian song and to determine its position within the history of the genre. Mendelssohn’s ideal of a poetic fusion of text and music, in which the music offers a more decisive (“bestimmt”) interpretation of the poetic text, led him to explore a wide array of stylistic options, allowing him to subtly transgress and transform the boundaries of the genre.